Nobiletin promotes fracture healing by modulating macrophage polarization: a review - Zhang, Zhiqi; Liu, Shangyi; Li, Wenhao; Shou, Kangquan (Frontiers in Pharmacology, 2026)
Fracture healing is a complex process in which various cells, including macrophages, are involved. M1 macrophages and the cytokines they secrete exacerbate local inflammation and inhibit fracture healing, whereas M2 macrophages inhibit inflammation and promote tissue repair. An imbalance in the ratio of M1 to M2 macrophages leads to delayed healing and nonunion of the fracture. Nobiletin has received increasing attention in promoting fracture healing. Thus, the aim of this review article was to investigate the effects of nobiletin on macrophages during fracture healing, with a major focus on the potential mechanisms and applications, and to provide a reference for further research on this compound.